Compromised : [compact disc, unabridged] counterintelligence and the threat of Donald J. Trump - Strzok, Peter, 1970- (Houghton Mifflin Harcourt, 2020)
The FBI veteran behind the Russia investigation draws on decades of experience hunting foreign agents in the United States to lay bare the threat posed by President Trump.